PENURUNAN KANDUNGAN BOD, COD, TSS, WARNA DAN PENGENDALIAN pH LIMBAH CAIR BATIK MENGGUNAKAN PROSES ELEKTROKOAGULASI TAHUN 2015 - Novika Hildayanti; Sudjarwo .; Fitri Rokhmalia (Poltekkes Kemenkes Surabaya, 2016)
Home industry batik is among the largest producers of liquid waste originating from the dyeing process. Those home industries discharge liquid waste to the surrounding water determine the capability of electrocoagulation to reduce the contents of BOD, COD, TSS, color and pH of liquid water from batik home industry.Electrocoagulation was used in the study with a stainless steel anode and an aluminium cathode.Result showed a decrease in BOD content from 855,85mg/l at minute 30 to 54,42 mg/l at minute 180. There was decrease in COD content from 1685,9mg/l at minute 30 to 98,30 mg/l at minute 180. There was decrease in TSS content from 720 mg/l at minute 30 to 50 mg/l at minute 180. There was decrease in color content from 242 TCU at minute 30 to 10,66 TCU at minute 180. An increase in pH of 6,9 occurred from minute 30 and remained stable for next minutes.They goverment is recommended to use electrocoagulation equipment since it fairly effective to reduce the contents of BOD, COD, TSS, color and pH in order for the liquid batik waste to meet the quality standards of Eat Java Governor Regulation No. 72 of 2013. Electrocoagulation equipment is quite easy to make and it can be designed according to local people conditions.